Synergistic role of in-situ Zr-doping and cobalt oxide cocatalysts on photocatalytic bacterial inactivation and organic pollutants removal over template-free Fe2O3 nanorods. (January 2023) - Manikandan, Velu; Anushkkaran, Periyasamy; Hwang, In-Seon; Chae, Weon-Sik; Lee, Hyun-Hwi; Choi, Sun Hee; Mahadik, Mahadeo A.; Jang, Jum Suk
Abstract: Herein, we synthesized in-situ Zr-doped Fe2 O3 NRs photocatalyst by successive simple hydrothermal and air quenching methods. The synergistic roles of CoOx (1 wt%) and Zr-doping on bacteria inactivation and model organic pollutants over Fe2 O3 NRs photocatalyst were studied in detail. Initially, rod-like Zr ((0–8) %)-doped Fe2 O3 NRs were produced via a hydrothermal method. CoOx was loaded onto the Zr ((0–8) %)-doped Fe2 O3 NRs) surface by a wet impregnation approach. The Zr-doping conditions and CoOx loadings were judiciously optimized, and a highly photoactive CoOx (1 wt%)/Zr(6%)-doped Fe2 O3 NRs photocatalyst was developed. The CoOx (1 wt%) loaded Zr(6%)-doped Fe2 O3 NRs photocatalyst revealed 99.4% inactivation efficiency compared with (0, 4 and 8)% Zr-doped Fe2 O3 NRs, respectively. After CoOx (1 wt%)/Zr(6%)-doped Fe2 O3 NRs photocatalyst treatment, Bio-TEM images of bacterial cells showed extensive morphological deviations in cell membranes, compared with the non-treated ones. Additionally, the optimum CoOx (1 wt%)/Zr(6%)-doped Fe2 O3 NRs photocatalyst exhibited 99.2% BPA and 98.3% orange II dye degradation after light radiation for 3 h. This work will provide a rapid method for the development of photostable catalyst materials for bacterial disinfection and organic degradation. Graphical abstract: Image 1 Highlights: In-situ Zr-doped Fe2 O3 NRs photocatalyst has been developed via a hydrothermal approach. CoOx loaded onto Zr ((0–8)%)-doped Fe2 O3 NRs) surface by a wet impregnation approach. Synergistic roles of CoOx (1 wt%) and Zr-doping on bacteria inactivation and organic pollutants were studied in detail. CoOx (1 wt%)/Zr(6%)-doped Fe2 O3 NRs revealed 99.4% E-coli and S. Aureus inactivation efficiency. Optimum photocatalyst exhibited 99.2% BPA and 98.3% orange II dye degradation within 3 h.